Hello Democrats Welcome to Chicago - Richard J. Daley:::::: (1968)
This booklet, prepared by Mayor Richard J. Daley for delegates to the 1968 Democratic National Convention, highlights Chicago's extensive urban development and modernization efforts. It showcases major housing, architectural, and renewal projects such as Carl Sandburg Village, Marine City, Lake Point Tower, and the Hyde Park-Kenwood Conservation Area, emphasizing public-private partnerships and middle-income housing growth. The publication also details infrastructure achievements, including O'Hare International Airport, the Eisenhower Expressway, water filtration systems, and new civic buildings, presenting Chicago as a leader in transportation, engineering, and urban planning. Social initiatives are prominently featured, particularly youth programs like the 1968 "Reach Out" campaign, expanded health services, anti-pollution efforts, and improved public safety systems. Overall, the booklet portrays Chicago as a forward-looking city committed to economic growth, cultural vitality, and improved quality of life for its residents during a period of significant national attention.